Attosecond Time-Resolved Autoionization of Argon - Wang, He; Chini, Michael; Chen, Shouyuan; Zhang, Chang-Hua; He, Feng; Cheng, Yan; Wu, Yi; Thumm, Uwe; Chang, Zenghu (My University, 2010)
Autoionization of argon atoms was studied experimentally by transient absorption spectroscopy with isolated attosecond pulses. The peak position, intensity, linewidth, and shape of the 3s3p6np 1P Fano resonance series (26.6–29.2 eV) were modified by intense few-cycle near infrared laser pulses, while the delay between the attosecond pulse and the laser pulse was changed by a few femtoseconds. Numerical simulations revealed that the experimentally observed splitting of the 3s3p64p 1P line is caused by the coupling between two short-lived highly excited states in the strong laser field.